Status of Serum bilirubin, Serum Proteins and Prothrombin time in babies with Perinatal Asphyxia (Journal of Dhaka National Medical College & Hospital, 2013)
Background and Objectives: Because of hypoxemia, different organ systems of the body are affected in perinatal asphyxia. This study was carried out to see the status of Serum bilirubin, Serum Proteins and Prothrombin time in asphyxiated babies and to know any correlation existing between hepatic dysfunction and the severity of perinatal asphyxia. Methods: A total of 70 full-term asphyxiated newborns (study group) were studied during January 2008 to December 2008 in the department of Paediatrics, Mymensingh Medical College Hospital. After enrolment these babies were grouped according to Sarnat & Sarnat stages of HIE as stage I, II & III (Sarnat & Sarnat 1976). Babies who are small for gestational age, having severe jaundice, sepsis or congenital anomalies of the hepatobiliary system were excluded from the study. A total of 50 healthy newborns were also studied as reference group. Two c.c. of venous blood were taken both from asphyxiated and healthy babies between 2nd and 5th day of life to estimate Total serum bilirubin (TSB), Serum Total protein (STP), Serum Albumin and Prothrombin time (PT). Data were analyzed by computer software SPSS version 15. Unpaired students t test was used to measure the level of significance and Spearmans rank correlation was done to see the correlation and at P < 0.05 the results were considered significant. Results: The mean TSB, STP & S. Albumin of asphyxiated babies were 5.52 ± 2.01mg/dl, 55.74 ± 8.84 & 32.60 ± 5.48 g/L respectively and those of normal babies were 4.51 ± 1.19 mg/dl, 66.30 ± 10.36 & 40.90 ± 6.45 g/L respectively and these differences were statistically significant (P < 0.001). On the other hand no significant changes were noted in prothrombin time. The rise of PT showed a significant positive correlation with the severity of perinatal asphyxia. On the other hand STP, S. Albumin & TSB showed no significant correlation. Conclusion: This study concludes that TSB, STP & S. Albumin significantly elevated and this elevation was proportional to the severity of perinatal asphyxia. On the other hand no significant changes were noted in prothrombin time. Recommendation: A large scale multi-centre study is recommended to establish this finding. DOI: http://dx.doi.org/10.3329/jdnmch.v18i2.16022 J. Dhaka National Med. Coll. Hos. 2012; 18 (02): 43-46